Prediction of maximum earthquake magnitude for northern Vietnam region based on the gev distribution - Hoan*, Vu Thi; Lu, Ngo Thi; Rodkin, Mikhail; Tuyen, Nguyen Huu; Hang, Phung Thi Thu; Phuong, Tran Viet (Vietnam Journal of Earth Sciences, 2016)
The present work is a continuation and improvement of the application of the generalized extreme value distribution to study the seismicity of the Southeast Asia. We have applied the generalized extreme value distribution (GEV) method to estimate maximum magnitude value (Mmax) for the earthquake catalog of Northern Vietnam. Using this method, we obtain the distribution of maximum earthquake magnitude values. This distribution can be characterized by its quantile Qq(τ) at any desirable statistical level q. The quantile Qq(τ) provides a much more stable and robust characteristic than the traditional absolute maximum magnitude Mmax (Mmax can be obtained as the limit of Qq(τ) as q → 1, τ → ∞). The parameters have been obtained: z = - 0.178 ± 0.08 ; s = 0.23 ± 0.08; m = 4.39 ± 0.16; Mmax = 6.8 with the probability of 98% for period 2014 - 2064. References Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Pham Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone. Journal of Sciences of the Earth, 35(1), 49-53. Cao Dinh Trong, Le Van Dung, Pham Nam Hung, Mai Xuan Bach, 2013. The neural network method for intermediate earthquake prediction (example in Vietnam). Journal of Marine Science and Technology, 3A(13), 17-24. Gumbel E. J, 1958. Statistics of Extremes, Columbia Univ. Press. Ngo Thi Lu, Tran Viet Phuong, 2012. About the approach to building algorithms and processes to predict earthquakes by statistical model. Journal of Sciences of the Earth, 34(4), 535-541. Ngo Thi Lu, Tran Viet Phuong, 2013. Building a new algorithm of the program for separation of forshock and aftershock groups from earthquake catalog to ensure the independence of the events. Journal of Marine Science and Technology. 3A(13), 79-85. Ngo Thi Lu, Tran Viet Phuong, 2016a. Prediction earthquake (time, location and magnitude of an earthquake) for the Northwest region of Vietnam by program’s VAST. ĐL.01/14-16. Thematic reports, 14 pages. Nguyen Hong Phuong, 1991. Probabilistic assessment of earthquake hazard in Vietnam based on seismotectonic regionalization. Tectonophysics, 198, 81-93. Nguyen Hong Phuong, 1997. Estimation of maximum earthquake magnitudes for seismic source zones of Vietnam using probabilistic methods. Contributions of marine geology and geophysics, 3, 48-65. Science and technics publishing house. Hanoi. Nguyen Hong Phuong, 2001. Probabilistic Seismic Hazard Assessment Along the Southeastern Coast of Vietnam, Natural Hazards 24, 53-74. Nguyen Hong Phuong, Pham The Truyen, 2014. Probabilistic Seismic Hazard Assessment for the South Central Vietnam. Vietnam J. Earth Sci., 36(4), 451-461. Nguyen Ngoc Thuy, 2005. Project report of KC. 08. 10: “Zoning detailed forecast earthquake in the Northwest of Vietnam”, 547p. Phan Trong Trinh , Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth-Science Reviews, 114, 224-235. Phan Trong Trinh , Hoang Quang Vinh, Nguyen Van Huong, Ngo Van Liem, 2013. Active fault segmentation and seismic hazard in Hoa Binh reservoir, Vietnam. Cent. Eur. J. Geosci. 5(2), 223-235. Pham Van Thuc and Kijko, A., 1985. Estimation of maximum magnitude and seismic hazard in Southeast Asia and Vietnam. Acta Geophys. Pol., XXX111(4), 377-387. Pisarenko V.F and Rodkin M.V, 2007. Distributions with Heavy Tails: Application to the Analysis of catastrophes, Coputational Seismology issue 38, 242p. Pisarenko V.F, Sornette A, Sornette D and Rodkin M.V, 2008. New approach to the Characterization of Mmax and of the Tail of the Distribution of Earthquake Magnitudes. Pure and Applied Geophysics, 165, 847-888. Pisarenko V.F, Sornette D and Rodkin M.V, 2010. Distribution of maximum Earthquake magnitudes in future time intervals: application to the seismicity of Japan (1923-2007). EPS (Earth, Planets and Space), 62, 567-578. Pisarenko V.F, Rodkin M.V, Ngo Thi Lu, 2012. New general quantile approach to the seismic risk assessment application to the Vietnam region. Proceedings of the international scientific conference, 161-167. Pisarenko V.F, Rodkin M.V, and Rukavishnikova T. A, 2014a. Estimation of the Probability of Strongest Seismic Disasters Based on the Extreme Value Theory. Physics of the Solid Earth, 50(3), 311-324. Pisarenko V.F, Sornette A, Sornette D and Rodkin M.V, 2014b. Characterization of the Tail of the Distribution of Earthquake Magnitudes by Combining the GEV and GPD Descriptions of Extreme Value Theory. Pure Appl. Geophys. 171, 1599-1624. Vu Thi Hoan, Ngo Thị Lu, M.V. Rodkin, Tran Viet Phuong, 2014. Application of the generalized extreme value distribution to study the seismicity of the Southeast Asian. Journal of Geology. Series A, 2014, 341-345. Hanoi, 180-189. Http://www.isc.ac.uk/iscbulletin/search/bulletin/